(untitled) - Bakker, Age F. B. (London, 1996)
This book surveys the financial and monetary functions of international financial institutions providing clear insights into how the institutions function, and how they influence, and are influenced by, practical economic policy-making
Keywords: Financial institutions, international,Tổ chức tài chính, quốc tế